Beyond diagnosis: symptom patterns across complex PTSD and borderline personality disorder - Simon, Joe J.; Spiegler, Kristin; Coulibaly, Kadiatou; Stopyra, Marion A.; Friederich, Hans-Christoph; Gruber, Oliver; Nikendei, Christoph (Frontiers in Psychiatry, 2025)
BackgroundComplex post-traumatic stress disorder (cPTSD) and borderline personality disorder (BPD) share overlapping clinical features, complicating accurate diagnosis and treatment. This overlap has fueled ongoing discussions regarding whether cPTSD and BPD should be considered as distinct diagnostic categories. To contribute to this debate, the current study aimed to clarify symptomatic similarities and differences between cPTSD and BPD using psychometric assessments.Methods97 female participants were recruited, including 34 patients with cPTSD, 25 with BPD and 38 healthy controls. All participants completed a battery of validated psychometric instruments assessing depression, anxiety, difficulties in emotion regulation, psychodynamic dysfunction, guilt-related distress, health-related functioning, as well as trauma-related symptoms and borderline personality traits. Differences between groups were analyzed using one-way ANOVAs, followed by post-hoc comparisons.ResultsPatients with cPTSD reported significantly higher levels of trauma exposure, posttraumatic symptom severity, dissociative symptoms, affective symptoms and functional impairment compared to both BPD patients and healthy controls. In contrast, no significant differences were found between cPTSD and BPD in borderline symptom severity, anxiety, difficulties in emotion regulation, guilt-related distress and psychodynamic dysfunction.ConclusionsThe results highlight trauma-related symptoms as key differentiators between cPTSD and BPD, supporting the conceptualization of cPTSD as a distinct disorder. However, as ICD-11 specific diagnostic instruments were not applied, the findings should be interpreted with appropriate caution.